The Influence of Price and Personal Selling on the Achievement of Housing Product Sales - Irninta Islamiah Yusran; Muhammad Aqsa; S. Sapar (PT Mattawang Mediatama Solution, 2022)
This study aimed to determine the effect of price and personal selling on the achievement of housing product sales. The method used in this research is quantitative with SEM analysis techniques using the Smart-PLS 3.3 application. The data instrument is the respondent's questionnaire with a sample of 60 people interested in buying Regency Palopo Hill Inc. The result of this research is that price affects sales achievement with a value of t count = 2.678 > t table = 1.670 with a P-Value of 0.008 or less than the Cut off Value of 0.05. While personal selling has no significant effect on the achievement of sales, the value of t count = 0.328 < t Table: 1.670 with a P-Value of 0.743 > 0.05.